Change in body mass index and insulin resistance after 1-year treatment with gonadotropin-releasing hormone agonists in girls with central precocious puberty - Jina Park; Jae Hyun Kim (Korean Society of Pediatric Endocrinology, 2017)
PurposeGonadotropin-releasing hormone agonist (GnRHa) is used as a therapeutic agent for central precocious puberty (CPP); however, increased obesity may subsequently occur. This study compared body mass index (BMI) and insulin resistance during the first year of GnRHa treatment for CPP.MethodsPatient group included 83 girls (aged 7.0-8.9 years) with developed breasts and a peak luteinizing hormone level of ≥5 IU/L after GnRH stimulation. Control group included 48 prepubertal girls. BMI and insulin resistance-related indices (homeostasis model assessment of insulin resistance [HOMA-IR] and quantitative insulin sensitivity check index [QUICKI]) were used to compare the groups before treatment, and among the patient group before and after GnRHa treatment.ResultsNo statistical difference in BMI z-score was detected between the 2 groups before treatment. Fasting insulin and HOMA-IR were increased in the patient group; fasting glucose-to-insulin ratio and QUICKI were increased in the control group (all P<0.001). In normal-weight subjects in the patient group, BMI z-score was significantly increased during GnRHa treatment (−0.1±0.7 vs. 0.1±0.8, P<0.001), whereas HOMA-IR and QUICKI exhibited no differences. In overweight subjects in the patient group; BMI z-score and HOMA-IR were not significantly different, whereas QUICKI was significantly decreased during GnRHa treatment (0.35±0.03 vs. 0.33±0.02, P=0.044).ConclusionGirls with CPP exhibited increased insulin resistance compared to the control group. During GnRHa treatment, normal-weight individuals showed increased BMI z-scores without increased insulin resistance; the overweight group demonstrated increased insulin resistance without significantly altered BMI z-scores. Long-term follow-up of BMI and insulin resistance changes in patients with CPP is required.